دراسة التداخلات الجزيئية لمجموعة من المركبات الحلقية السداسية مع النايترو ميثان وذلك بقياس الكثافة ومعامل الانكسار عند درجة حرارة 298.15 كلفن (مجلة ديالى للبحوث الانسانية, 2022)
Nitro methane is an aprotic solvent with high polarity Which is used in a variety of applications(l) There is many   .project between nitromethane and many kind of R - OH and Ar-OH at diffract temperature. But Less then between nitromethane and cyclic compound.